The role of deception reduction in controlling some kinetic abilities and basic skills in badminton for female students - Nezar Mahmood, Raheeq; Alwan, Nihad Mohammed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this paper was to identify the role of deception reduction in controlling some kinetic abilities and basic skills in badminton for female students. The researchers used the descriptive approach for its suitability to the problem and objectives of the research. The 34 female students of the first stage at the Al-Salam University defined the research community and the final sample consisted of 30 female students. The researchers used the Statistical Package for the Social Sciences (SPSS) for data analysis. Based on the results, there is a statistically significant relationship between control deception and motor abilities (agility, balance and coordination) (p < 0.05), as well as a statistically significant relationship between control deception and basic skills (serving, forehand and backhand) (p < 0.05). Through the results, it was concluded the need to reduce deception in badminton players in order to achieve better performance.